Surface Properties of LaNi5 and TiFe—Future Opportunities of Theoretical Research in Hydrides - Łodziana, Zbigniew (Frontiers in Energy Research, 2021)
Hydrogen in the solid state compounds is still considered as a safe method of energy storage. The ultimate metal hydrides or other materials that can be used for this purpose remain unknown. Such metal hydrides shall have favorable thermodynamics and kinetics of hydrogen ad/desorption, and it shall be resistant to contamination of H2 and should not constitute any environmental hazards. Theoretical investigations, based on quantum mechanics approach, have a well-established position in modern materials research; however, their application for design of new alloys with tailored properties for reversible hydrogen storage is rarely present in the literature. The mainstream research deals with accurate prediction of thermodynamic and structural properties of hydrides as a function of composition or external parameters. On the other hand, the kinetic effects related to hydrogen transport or interaction between solid and pure or contaminated H2 are more demanding. They cannot be easily automated. We present calculations of the equilibrium crystal shapes for LaNi5 and TiFe—two important materials that show reversible hydrogen cycling near ambient conditions. Understanding of the surface properties is crucial for development of materials with better cyclability or resistance to hydrogen impurities. Indeed, the calculated adsorption energy of carbon oxides or water is stronger than hydrogen. These molecules block the active sites for H2 dissociation, leading to formation of surface oxides. Particularly strong adsorption of CO/CO2 on TiFe explains large degradation of hydrogen storage capacity of this compound by carbon oxides. Over-representation of La on exposed facets of LaNi5 is related to formation of La2O3 and La(OH)3. Such examples show that the present development of computational methods allows reliable studies of intermetallic properties related to their surface or novel catalytic applications.